Muslim consumers’ behaviour towards 'pork-free' and 'no pork' signs displayed at non-certified halal restaurants in Shah Alam, Selangor - Md Idris, Aini Sa’adah; Che Hassan, Nurul Hidayah; Abdul Rasol, Lokman; Wan Ahmad, Wan Azmi; Jaafar, Abu Bakar; Zakaria, Nadisah (Journal of Islamic, Social, Economics and Development, 2025)
This paper investigates the consumer behaviour of Muslim consumers in Shah Alam, Selangor, towards signage 'Pork Free' and 'No Pork' in non-certified Halal restaurants. The study also explores the influence of awareness of the Halal concept on consumer behaviour in relation to such signage. A cross-sectional survey was conducted, collecting data from 384 respondents using a Likert scale questionnaire. Descriptive analysis was employed to summarize and interpret the data. The findings indicate that participants expressed a tendency towards agreement regarding the importance of knowing if an uncertified Halal restaurant serves pork and the significance of 'no pork' or 'pork-free' signs in choosing a restaurant. However, there was relatively lower agreement on the belief that such signage indicates a restaurant's Halal status. Recommendations are provided to enhance consumer awareness, encourage Halal certification, and foster transparent information sharing to address the 'pork-free' signage issue and promote responsible practices in the Halal food industry. The study contributes to a deeper understanding of consumer behaviour and highlights the importance of informed dining choices among Muslim consumers’ in Shah Alam.